Wenxin Keli regulates energy metabolism and improves Cx43 via the AMPK/SIRT1/PGC-1α pathway - Cui, Xiyuan; Lou, Lixia; Nie, Bo; Zhao, Yizhou; Zhao, Jiuli; Yang, Ding; Wang, Zhe; Zheng, Shaoqing; Wu, Aiming (Frontiers in Pharmacology, 2025)
BackgroundResearch has underscored the significance of targeting energy metabolic remodeling in heart failure (HF) as a crucial therapeutic avenue in recent years. Following the onset of heart failure, dysregulated energy metabolism induces multiple adverse effects, exemplified by the reduced expression of connexin 43 (Cx43)—a gap junction protein requiring substantial ATP for phosphorylation modification—in rats with post-myocardial infarction (MI) heart failure. In this study, we report that Wenxin Keli (also known as Wenxin granule), a clinically available Chinese patent medicine used for preventing and treating heart failure–related arrhythmias, modulates energy metabolism and improves Cx43 function by activating AMPK/SIRT1/PGC-1α signaling pathway. However, the pathological alterations after heart failure are intricate, and the underlying mechanism through which Wenxin Keli exerts its therapeutic effect on heart failure remains to be further elucidated.MethodsA post-myocardial infarction heart failure rat model was established via left anterior descending coronary artery ligation. Cardiac function was evaluated 4 weeks later using echocardiography, HE, and Masson trichrome staining. ELISA was employed to detect energy metabolism-related indices, while WB analysis was used to quantify the expression levels of proteins, including SIRT1, PGC-1α, and Cx43. IHC was further utilized to assess Cx43 protein content in tissue sections. Ventricular fibrillation (VF) was induced to determine the VF threshold, providing insights into arrhythmogenic susceptibility.ResultsWenxin Keli enhances energy metabolism and improves Cx43 function in post-MI heart failure rats by activating the AMPK/SIRT1/PGC-1α signaling pathway. Specifically, Wenxin Keli stimulates the SIRT1/PGC-1α axis, promoting interaction between PGC-1α and PPARs and ERRs. This dual mechanism addresses the combined impairments in fatty acid oxidation and glucose utilization after heart failure, restoring mitochondrial oxidative phosphorylation and increasing ATP production through the TCA cycle. Furthermore, Wenxin Keli boosts the positive regulatory effect of SIRT1 on PGC-1α by upregulating AMPK phosphorylation, thereby further activating the AMPK/SIRT1/PGC-1α signaling pathway and creating a positive feedback loop.ConclusionWenxin Keli exhibits multi-target regulation of energy metabolic disorders in post-myocardial infarction heart failure while protecting Cx43. Its core mechanism is activating the AMPK/SIRT1/PGC-1α signalling pathway and its downstream regulatory network.